2011
DOI: 10.1016/s1995-7645(11)60070-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant activities of selected seaweeds from Southeast coast of India

Abstract: The seaweeds could be considered for curing diseases from oxidative deteriorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 44 publications
7
53
2
5
Order By: Relevance
“…The organism Serratia marcescens was resistant to the extracts, showing only mild sensitivity with Daniella oliveri, Ceiba pentandra, Jatropha tanjorensis extracts at undiluted concentrations only. This finding is in agreement with earlier report by [29] [30].…”
Section: Discussionsupporting
confidence: 94%
“…The organism Serratia marcescens was resistant to the extracts, showing only mild sensitivity with Daniella oliveri, Ceiba pentandra, Jatropha tanjorensis extracts at undiluted concentrations only. This finding is in agreement with earlier report by [29] [30].…”
Section: Discussionsupporting
confidence: 94%
“…Statistical significance was, however, observed in all tested concentrations (p < 0.05) among all algal species based on individual absorbance. On the other hand, results of reducing power reported here are much lower than those cited for a variety of seaweeds, such as Enteromorpha compressa (Ganesan et al, 2011), Kappaphycus alvarezii , and Turbinaria conoides (Devi et al, 2011).…”
Section: Tpc Valuescontrasting
confidence: 93%
“…Some studies showed also a low activity in water extracts [47][48]. However, water extracts generally had higher ferrous chelating activity than 70% acetone extracts and no correlation was found with this TPC, suggesting other components such as polysaccharides, proteins or peptides in the extracts [49]. Our result is in accordance with this study, which also reported a high Fe2+ chelating activity of water extracts, specially with the brown algae H. scoparia wich attained the highest activity (FIC) during the three seasons comparing with S. coronopifolius wich had the highest total phenolic content.…”
Section: Discussionmentioning
confidence: 90%